2019
DOI: 10.3390/nu11081895
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Donor Milk for Very Preterm Infants Decreased the Risk of Necrotizing Enterocolitis without Adversely Impacting Growth or Rates of Breastfeeding

Abstract: Human milk contains non-nutritional factors that promote intestinal maturation and protect against infectious and inflammatory conditions. In the Neonatal Intensive Care Unit (NICU) setting, donor milk (DM) is recommended when availability of own mother’s milk (OMM) is not enough. Our aim was to compare the incidence of necrotizing enterocolitis (NEC) and late-onset sepsis (LOS) in very preterm infants (VPI) after the introduction of DM. Growth and breastfeeding rates were examined as secondary outcomes. Singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…In a large monocentric study designed as an interrupted time series study, Alshaikh et al [ 12 ] showed that a human milk quality improvement initiative to implement the rate of human milk in the neonatal intensive care unit was associated with a lower risk of developing NEC (OR = 0.32; 95% confidence interval 0.11–0.93). Similar results were found in a recent study conducted by Cañizo Vázquez et al [ 13 ], in which infants who received donor human milk had a decreased incidence of NEC compared to formula-fed infants (9.1% vs. 3.4%, p = 0.055), especially among the group of infants born at a gestational age between 28 and 32 weeks (5.4 vs. 0.0%, p = 0.044).…”
Section: Human Milk and Comorbiditiessupporting
confidence: 89%
“…In a large monocentric study designed as an interrupted time series study, Alshaikh et al [ 12 ] showed that a human milk quality improvement initiative to implement the rate of human milk in the neonatal intensive care unit was associated with a lower risk of developing NEC (OR = 0.32; 95% confidence interval 0.11–0.93). Similar results were found in a recent study conducted by Cañizo Vázquez et al [ 13 ], in which infants who received donor human milk had a decreased incidence of NEC compared to formula-fed infants (9.1% vs. 3.4%, p = 0.055), especially among the group of infants born at a gestational age between 28 and 32 weeks (5.4 vs. 0.0%, p = 0.044).…”
Section: Human Milk and Comorbiditiessupporting
confidence: 89%
“…In neonatal intensive care units necrotising enterocolitis (NEC) remains a continuing problem. Wherever possible breastmilk is given to the infant and reduces the incidence of NEC [75,76]. A meta-analysis suggests that unlike breastmilk, donor human milk is not effective in the prevention of NEC [77].…”
Section: Neonatal Sepsismentioning
confidence: 99%
“…Donor milk, while arguably preferable to bovine-based formula [19], loses effectiveness through the pasteurization process, and is also not age-matched to the developmental stage of the infant to whom it is donated [20,21]. Thus, studies utilizing donor HM have shown mixed results when examining utility in protection against preterm pathogens, NEC, and mortality [22][23][24].…”
Section: Introductionmentioning
confidence: 99%